POLITICAL CAMPAIGN STRATEGIES IN THE DIGITAL AGE: A LITERATURE REVIEW OF SOCIAL MEDIA PRACTICES - Bikah Kusti Noviani; Edy Sijaya; Hasman Umuri (INJOSEDU: International Journal of Social and Education, 2025)
Political campaigning in the digital age has undergone major changes. Social media is now an important tool in politicians' campaign strategies. This paper reviews the various ways politicians use social media to campaign. From Facebook to TikTok, politicians utilise online platforms to reach out to voters. They share their visions, programmes and activities directly to voters' smartphones. In addition, social media is also used to fundraise and organise supporters. However, the use of social media in politics also creates new problems. It has become easier to spread fake news and manipulate public opinion. Voter data privacy is also a serious concern. Nevertheless, social media remains an important part of modern campaigning. Politicians who are good at utilising it can benefit greatly. In the future, expertise in digital campaigning will be increasingly crucial for anyone who wants to succeed in politics.